Soul graffiti : - Scandrette, Mark (Jossey-Bass, 2007)
In Soul Graffiti, Mark Scandrette strips away the religious traditions that cloud our view of Jesus and gives us the courage to investigate the transformational message. If the challenge for churches and for individual followers of Christ is to live out the gospel, this is the help we need